PENGARUH TARIF PAJAK, KESADARAN DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR DI KOTAAMBON - Silooy, Revy Wilhelmina (Jurnal Akuntansi, 2021)
Motor vehicle tax is a vehicle tax that contributes to local government revenue so that the greater the level of taxpayer compliance in paying motorized vehicle taxes, the motor vehicle tax revenue received by local governments will also increase. This research is an empirical study which aims to determine the compliance of tax rates, awareness of paying taxes and tax sanctions on taxpayer compliance in paying motorized vehicle taxes in Ambon city. This study uses primary data using a questionnaire instrument distributed to motor vehicle taxpayers registered at the SAMSAT office of Ambon City. Samples from the population taken were 100 respondents. The sampling technique used in this study was the Slovin technique. Data analysis used Descriptive Statistics, Data Quality Test, Classical Assumption Test, Multiple Linear Regression. Based on the results of hypothesis testing, it can be concluded that the tax rate variable (X1) does not have a significant effect on taxpayer compliance (Y), while the awareness variable (X2) and tax sanctions (X3) have a significant effect on taxpayer compliance (Y)